Support for the continuous education system for medical personnel in the scope of geriatric care - a project co-funded by the European Social Fund as part of the Human Capital Operational Programme - Cholewka, Beata; Zinkowska, Dorota; Majsterek, Ewa (Nursing in the 21st Century, 2012)
SUPPORT FOR THE CONTINUOUS EDUCATION SYSTEM FOR MEDICAL PERSONNEL IN THE SCOPE OF GERIATRIC CARE - A PROJECT CO-FUNDED BY THE EUROPEAN SOCIAL FUND AS PART OF THE HUMAN CAPITAL OPERATIONAL PROGRAMME Introduction. Ageing of societies is an important problem for Europe, including Poland. Therefore healthcare in Poland should be adapted to the current demographic trends. One of the main goals of a healthcare policy should be to maintain such a level of psychical and physical fitness of the elderly, which would enable them to remain professionally active as long as possible and thus maintain their economic contribution and lower the degree of demographic burden on the national economy. One of the conditions of introducing system measures, the goal of which would be to improve the level of care for the elderly in Poland, would surely be to improve the level of education of medical staff in the field of geriatrics. In the years 2012-2015 the Department of Nurses and Midwives of the Polish Ministry of Health, together with the Medical Postgraduate Training Centre, will carry out a system project, the goal of which will be to improve the level of care provided to the elderly in Poland by raising the level of competence (through training) of medical staff in the scope of geriatric care. The training provided as part of the project shall encompass general practitioners, general care nurses, physiotherapists, healthcare aides and community therapists. Aim. The goal of the study is to present the general assumptions of the system project under the name Support for the continuous education system for medical personnel in the scope of geriatric care, which is co-funded by the European Social Fund as part of the Human Capital Operational Programme.